Effect of a dementia education intervention on the confidence and attitudes of general practitioners in Australia: a pretest post-test study - Mason, Ron (BMJ Open, 2020)
OBJECTIVES: This study assessed the impact of a Dementia Education Workshop on the confidence and attitudes of general practitioner (GP) registrars (GPR) and GP supervisors (GPS) in relation to the early diagnosis and management of dementia. DESIGN: Pretest post-test research design. SETTING: Continuing medical education in Australia. PARTICIPANTS: 332 GPR and 114 GPS. INTERVENTIONS: Registrars participated in a 3-hour face-to-face workshop while supervisors participated in a 2-hour-modified version designed to assist with the education and supervision of registrars. MAIN OUTCOME MEASURES: The General Practitioners Confidence and Attitude Scale for Dementia was used to assess overall confidence, attitude to care and engagement. A t-test for paired samples was used to identify differences from preworkshop (T1) to postworkshop (T2) for each GP group. A t-test for independent samples was undertaken to ascertain differences between each workshop group. A Cohen’s d was calculated to measure the effect size of any difference between T1 and T2 scores. RESULTS: Significant increases in scores were recorded for Confidence in Clinical Abilities, Attitude to Care and Engagement between pretest and post-test periods. GPR exhibited the greatest increase in scores for Confidence in Clinical Abilities and Engagement. CONCLUSIONS: Targeted educational interventions can improve attitude, increase confidence and reduce negative attitudes towards engagement of participating GPs.